Analysis of Mental Toughness Among Sub-Elite Field Hockey Players - Babu P (Journal of Physical Education and Sport Pedagogy, 2022)
Preparation is the key to success in sports at all levels, which is why professional athletes spend a lot of time and money to ensure adequate knowledge, quality of practice and physical education skills. However, among the elite, the difference between those who work well and those who work well is mainly their level of preparation and the ability to use their skills in High status. An important part of this mental preparation is developing the ability to cope with the mental stress that comes with participating in elite sports. In this solution, individual differences in how people respond to stress mean that each person can respond to stressful situations in their own way. This is because individuals can use various coping and coping strategies to cope with stress/anxiety (Holahan Moos, 1994; Moos Shaefer, 1993).Subjects were divided into four groups based on their performance at the 2011 South Division Intercollegiate Hockey Tournament in Tirunelveli. The total number of subjects is 72 and there are 18 subjects in each group. From this qualitative research, seven aspects of psychology were developed. These factors include: self-confidence, negative energy, emotional control, perception and thinking, motivation, positive energy and behavior control. ANOVA statistics were used to analyze the differences between groups. This article provides some information about the empowerment field—definition and theory. Rigorous scientific studies in this area of research allow us to better understand mental health. With an understanding of psychology, it is now possible to conduct research on life-long measurement, development, and education. To truly understand how resilience emerges in people's lives, future research will best examine the interactions between individual traits (e.g., the seven factors identified here), social support, and the nature of stress or depression.